Collaborative Governance: A Synergistic Effort to Overcome Waste Pollution in Beach Tourism Destinations - Garis, Regi Refian; Effendi, Safaranita Nur (Journal of Governance, 2025)
This study aims to examine the role of collaborative governance in overcoming waste pollution in Pangandaran Beach, as well as analyze government policies and stakeholder involvement. The method used is a literature study, which involves collecting and analyzing information from various academic sources and policies related to waste management. The theory applied in this study is the collaborative governance model developed by Ansell and Gash, which emphasizes initial conditions, institutional design, leadership, and collaboration processes. The results of the study indicate that collaboration between the government, the tourism industry, and the community is a crucial element in formulating effective policies. Although regulations related to waste management have been in place, their implementation still faces significant challenges, including a lack of coordination and effective law enforcement. The conclusion of this study emphasizes the need for efforts to strengthen synergy between stakeholders and stricter law enforcement in waste management. Through a more solid collaborative approach, it is hoped that waste pollution in Pangandaran Beach can be overcome sustainably so that the environment is maintained and tourism can develop well